The Views of Managers, Teachers, Students, and Parents About Visual Arts Education in Science and Art Centers - Usal, Yelda; Buyurgan, Serap (Ataturk Univ, 2022)
The purpose of the research is to determine the views of administrators, teachers, students, and parents regarding the building and physical equipment, education program and diagnosis in Visual Arts education given in Science and Art Centers. Research, in the academic years of 2016-2017 - 2017 and 2017-2018, - 2018, was carried out with 7 administrators and 12 teachers, 71 3rd and 4th grade students, and 70 parents working in 7 Science and Art Centers (Ankara, Trabzon, Hatay, & Idot;stanbul, & Idot;zmir, Elazi & gbreve;, Gaziantep) from 7 different regions of Turkey. In research, an explanatory mixed design, in which quantitative and qualitative research methods are used together, was used. Science and Art Center-Visual Arts Interview Questionnaire (B & Idot;LSEM-GSGA) was used to collect quantitative data, and a questionnaire and interview form Science and Art Center-Visual Arts Interview Form (B & Idot;LSEM-GSGF) was used to collect qualitative data. In the evaluation of quantitative data, descriptive statistical frequency and percentage, arithmetic mean, standard deviation, Kruskal Wallis H-Test and Mann Whitney U-test were used. The qualitative data of the research were analyzed by descriptive analysis method. Considering all the evaluation criteria, regarding the size of the building and physical equipment of the administrators, teachers, students, and parents, the schools are sufficient in terms of equipment, but they do not have an area outside the workshop to make Visual Arts practices. In their views on education programs, it would be more appropriate to give the lack of Visual Arts course hours and to give equal proportions of art and science courses. In the opinion about the diagnostic methods, it was concluded that it is not correct for a student who is diagnosed with artto take the exam from science.
Bilim ve Sanat Merkezlerinde Verilen Görsel Sanatlar Eğitimine Yönelik Yönetici, Öğretmen, Öğrenci ve Velilerin Görüşleri
Keywords: Giftedness/giftedness; visual arts education; visual art education in science and art centers